An Improved Version of Update Pheromone Rule of ACO algorithm for TSP - Savita, Ranjeet; Sharma, Pankaj; Gupta, Manish (International Journal of Computer Sciences and Engineering, 2019)
Ant colony optimization algorithm is a popular meta-heuristic optimization algorithm that has been proven successful for solving travelling salesman problem. In this paper, modified version of ant colony optimization for solving travelling salesman problem has been proposed. In this modified version, update pheromone phase of ant colony optimization algorithm is updated. Here, best distance is calculated by comparing all the nodes distance and taken the best distance for find next node instead of taking ants one by one and keep updating later on. This modified version improves the total cost as well as total time of travelling salesman problem. Proposed algorithm is performed on 51 cities, 61 cities, 70 cities and 76 cities problem. Comparative study shows that proposed algorithm is better than standard ant colony optimization algorithm.